Assessment of health impacts attributed to PM10 exposure during 2011 in Kermanshah City, Iran - Elahe Zallaghi; Mohammad Shirmardi; Zahra Soleimani; Gholamreza Goudarzi; Mohammad Heidari- Farsani; Ghassem Al-Khamis; Ali Sameri (Journal of Advances in Environmental Health Research, 2014)
The main aim of this study was to evaluate cardiovascular and respiratory outcomes attributed to PM10 in Kermanshah, Iran. In order to gather data, an Environmental Dust Monitor instrument was used at 3 stations throughout the city at a height of at least 3 m above the ground. We obtained an input file for the model from crude data and quantified PM10 using the AirQ model. Our estimation showed that 80% of cardiovascular deaths occurred on days with PM10 concentrations of less than 170 μgm-3. The number of respiratory deaths due to PM10 was estimated to be 46 people in 2011, showing a 48% reduction in such deaths compared to 2010. The number of patients with respiratory problems attributed to PM10 exposure comprised 5.61% of the total number of patients admitted to hospitals due to respiratory diseases. This lower percentage of morbidity and mortality attributed to suspended particles in Kermanshah in 2011, in comparison with 2010, was due to the higher exposure days with PM10 concentration of 200-250 μgm-3 in 2010. Every 10 μgm-3 increase in the concentration of suspended particles led to a 0.8 and 1.2% rise in the mortality rate due to cardiovascular and respiratory diseases, respectively. Additionally, the rates of heart and respiratory problems increased by 0.9 and 0.8%, respectively.